Incomplete Kawasaki Disease: A Rising Trend - Zainab, Madiha; Guha, Suparna (Journal of Nepal Paediatric Society, 2016)
Kawasaki Disease is the most common cause of acquired heart disease in the developed countries. The diagnosis of typical Kawasaki Disease (KD)is not much of a problem. However incomplete Kawasaki Disease where only two to three clinical features are present, poses a diagnostic dilemma. Here we report our experience with the disease in the paediatric department of Vivekananda Institute of Medical Sciences (VIMS). In one year retrospective study from Jan 2015 to Jan 2016, 20 cases were diagnosed as KD, of which five were complete and 15 incomplete. Fifty percent of cases were less than one year’s age and there was male preponderance. More than 90% showed echo changes and all except one responded to IVIG and aspirin who succumbed due to aneurysm rupture. So we conclude that high index of suspicion for diagnosing KD must be there and early treatment to prevent echocardiographic changes. J Nepal Paediatr Soc 2016;36(2):208-212